Community-Based Learning Orientation in Pesantren - Irma Hermawati; Saadah Nursaidah; Cecep Hilman (P3M IAI Nusantara Batang Hari, 2023)
Pesantren is one of the religious educational institutions that has gained trust among the people of Indonesia. The position of pesantren as an educational institution also received government recognition, as mentioned in article 1 paragraph 4 of PP no 55 of 2007 concerning Religious Education and Religious Education, that pesantren are community-based Islamic religious educational institutions. The purpose of writing this article is to discuss Community-Based Learning in Pesantren. The approach used is qualitative. The analyst method is library research which is literature-based research. The results of the discussion show that community-based education in Islamic boarding schools plays an important role in creating quality education and in accordance with community expectations. Through community-based learning, this means that the community takes responsibility and makes a real contribution to the development of education, so that the existence of this pesantren really brings benefits in the development of pesantren as a form of community-based educational institutions.